Coexistence of neurofibromatosis type-1 and primary pulmonary sarcoma: a case report and review of the literature - Boo, Yang Liang; Lim, Suat Yee; Chin, Pek Woon; Md Tarekh, Noor Aliza; Hoo, Fan Kee (Labome.Org, 2014)
Neurofibromatosis type-1 (NF1) is a genetic disorder characterized by café-au-lait spots, neurofibroma and other associated features. The risk of malignancy is approximately 2.5 to 4-fold higher as compared to general population. However, primary pulmonary sarcoma is rarely reported in patients with NF1. Here, we describe a case of NF1 complicated with primary pulmonary sarcoma.